The structure of glassy HgS–GeS₂ - Halyan, V.V.; Davydyuk, H.Ye.; Parasyuk, O.V.; Kevshyn, A.H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
The glass HgS(x)-GeS2(₁₀₀-x) (0 ≤ x ≤ 50) was subjected to X-ray analysis. The radial distribution functions were calculated using the integral Fourier transformation based on X-ray scattering curves. The average interatomic distances within the first and second coordination spheres were determined. It is suggested that the transformational changes of scattering curves are related to the emergence of heterogeneity due to Hg₄GeS₆ inclusions.